2021
DOI: 10.1038/s41524-021-00518-4
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of higher-order topological insulators using the spin Hall conductivity as a topology signature

Abstract: The discovery and realization of topological insulators, a phase of matter which hosts metallic boundary states when the d-dimension insulating bulk is confined to (d − 1)-dimensions, led to several potential applications. Recently, it was shown that protected topological states can manifest in (d − 2)-dimensions, such as hinge and corner states for three- and two-dimensional systems, respectively. These nontrivial materials are named higher-order topological insulators (HOTIs). Here we show a connection betwe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 48 publications
0
11
0
Order By: Relevance
“…They show that triangular nanoflakes with armchair edges present in-gap corner states with fractional charge, protected by C 3 symmetry. Besides being one of the striking features of a 2D-HOTI [39][40][41][42][43], they explain the presence of metallic edge states in the zigzag edges and connect them to the topology of the 2D material.…”
Section: Introductionmentioning
confidence: 88%
See 1 more Smart Citation
“…They show that triangular nanoflakes with armchair edges present in-gap corner states with fractional charge, protected by C 3 symmetry. Besides being one of the striking features of a 2D-HOTI [39][40][41][42][43], they explain the presence of metallic edge states in the zigzag edges and connect them to the topology of the 2D material.…”
Section: Introductionmentioning
confidence: 88%
“…Refs. [37,38] have recently revealed that some 2H-TMDs are 2D higher-order topological insulators (2D-HOTIs), not previously identified by the SHE signature [39]. They show that triangular nanoflakes with armchair edges present in-gap corner states with fractional charge, protected by C 3 symmetry.…”
Section: Introductionmentioning
confidence: 96%
“…Once the PAO Hamiltonian H PAO (k) is constructed we can calculate the orbital responses to an applied electric field using linear−response theory. This method have been used to investigate several other systems, ranging from topological to timedependent properties [62][63][64][65] 3. Electronic spectra of both models…”
Section: Ab-initio Simulationsmentioning
confidence: 99%
“…, where for the SH conductivity X η = ŝη and for the OH conductivity (OHC) X η = ˆ η ; ŝη and η represent the η-components of the spin and of the atomic angular momentum operators, respectively. This is implemented in the Paoflow code [40] that been successfully used o study topological materials [41,42], time dependent spin dynamics [43], among other topics. For our conductivity calculations we have increased the sampling to 200×200×1 k-points in the 2D B.Z.…”
Section: Introductionmentioning
confidence: 99%